2021
DOI: 10.3389/fspor.2021.637576
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Psychological Well-Being During the COVID-19 Lockdown: Relationships With Motivational Quality and Nature Contexts

Abstract: The COVID-19 pandemic is a global event that has already had substantive negative impacts on psychological well-being. This study investigated the relationship between physical activity (PA) and psychological well-being during a country-wide COVID-19 lockdown in New Zealand. Motivational quality and PA context (nature-based or non-nature-based) were included as potential mediating and moderating variables within this relationship, respectively. Participants completed an online survey assessing psychological we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 44 publications
(35 reference statements)
5
18
1
Order By: Relevance
“…This is in line with the large Mannheim Corona Study [35] but in contrast to the aforementioned study in German students [33]. Investigations from the first wave of the pandemic also found positive associations between PA and well-being [36,37]. However, it is not clear to what extent results from the first wave are generalizable to the second one.…”
Section: Discussionsupporting
confidence: 53%
“…This is in line with the large Mannheim Corona Study [35] but in contrast to the aforementioned study in German students [33]. Investigations from the first wave of the pandemic also found positive associations between PA and well-being [36,37]. However, it is not clear to what extent results from the first wave are generalizable to the second one.…”
Section: Discussionsupporting
confidence: 53%
“…Passmore and Howell (2014) also demonstrated that a 2week NPA intervention resulted in increased EWB and HWB, and in a series of survey studies, Wolsko et al (2019) found that NPA was associated with both EWB and HWB. However, other studies have found no significant difference between NPA and non-NPA with regards to EWB (e.g., Lawton et al, 2017) or HWB (e.g., Jenkins et al, 2021), respectively. While these mixed findings could be a result of different populations being sampled or different measurement tools (as suggested by Pritchard et al, 2020), it is also possible that intervening socio-psychological factors may influence the relationships between NPA and HWB and EWB, respectively.…”
Section: Introductionmentioning
confidence: 86%
“…This study utilised a cross-sectional survey design, hosted by the online survey platform Qualtrics. Participants were identified from a pool of respondents to a previous crosssectional survey study, which investigated the determinants and outcomes of physical activity as a result of the COVID-19 pandemic (Jenkins et al, 2021). This previous study used a convenience sampling method to recruit a sample of participants across the New Zealand population via mainstream social media platforms (Akers and Gordon, 2018), email lists and newsletters for universities and other large organisations (e.g., regional and national sports organisations, city councils), and a virtual snowball recruitment technique (Baltar and Brunet, 2012).…”
Section: Research Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to its benefits on mental health, physical activity may alleviate psychological disturbances related to pandemia, quarantine and social isolation. The benefits of physical activity on psychological well-being during the COVID-19 lockdown have been recently reported [39]. Therefore, whenever possible and provided that local and national COVID-19 restrictions are respected, people without any symptoms or diseases should be encouraged to exercise, preferably outdoors (walking, jogging, cycling, gardening).…”
Section: Physical Activitymentioning
confidence: 99%